Marketing Dynamics of Muslim MSMEs In Bengkulu Province: Product Innovation, Competitive Advantage, and Market Orientation in Improving Marketing Performance - Novrianda, Herry; Shar, Aan (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose:The purpose of this study is to explore the impact of business strategy development, mainly focusing on product innovation, competitive advantage, and market orientation, on the marketing performance of micro, small, and medium enterprises (MSMEs) in Bengkulu Province. The research emphasizes the importance of optimizing marketing performance to boost economic outcomes, not only for large enterprises but also for MSMEs, which play a significant role in local economies.Design/Methodology:This research utilizes a descriptive quantitative methodology to investigate the proposed relationships. A non-probability sampling technique, precisely the judgmental (purposive) method, was employed to select a sample of 500 owners or managers of MSMEs across various districts of Bengkulu Province, including Kaur, Seluma, Lebong, Kepahiang, and Central Bengkulu. The data were subjected to reliability and validity tests based on pre-test results, and multiple linear regression was applied to analyze the main hypotheses.Findings:The findings reveal that product innovation, competitive advantage, and market orientation all have a positive and significant influence on the marketing performance of MSMEs in Bengkulu Province. The results highlight the critical role these factors play in enhancing the marketing effectiveness of MSMEs, demonstrating that improvements in these strategic areas can lead to substantial gains in overall marketing performance.Practical Implications:The practical implications of this research suggest that MSME owners and managers should focus on strengthening their product innovation capabilities, leveraging competitive advantages, and adopting a more market-oriented approach to improve marketing performance. These strategies could drive economic growth and sustainability for MSMEs in Bengkulu Province, contributing to broader regional economic development.Originality/Value:This study offers valuable insights into the marketing performance of MSMEs in a developing region, specifically Bengkulu Province. By focusing on the combined impact of product innovation, competitive advantage, and market orientation, the research provides a comprehensive understanding of how these strategic elements influence MSME marketing outcomes. The originality lies in its application to a relatively under-researched context, offering practical recommendations for MSME development.